Cruise ship dining experiencescape: the perspective of female cruise travelers in the midst of the COVID-19 pandemic - Radic, Aleksandar; Luck, Michael; Al-Ansi, Amr; Chua, Bee Lia; Seeler, Sabrina; Han, Heesup (Elsevier, 2021)
The cruise dining experience is one of the core elements of the overall cruise travel experience as guests fulfill their cognitive and affective needs in this pleasant environment. Nonetheless, the cruise dining experience has been sparsely researched. There is also no holistic model conceptualizing the cruise ship dining experiencescape. This study explores how under the influence of the COVID-19 pandemic, cruise ship dining environment stimuli dimensions are evaluated by female cruise travelers. Female travelers are the major spenders and travel decision-makers. They are also the dominant customer group in the cruise sector. Their perception of cruise ship dining environment is leading to their positive emotional responses and approach behavior. More precisely, this study demonstrates the potency of the moderating role of a perceived health risk from COVID-19, which strengthens female travelers’ perceptions of the dining atmosphere and interaction with other guests by evoking positive emotions and influencing their approach behavior.